Industrial training report: Jayamas Property Sdn. Bhd. / Nur Athirah Junaidi - Junaidi, Nur Athirah (Universiti Teknologi MARA, Perlis, 2024)
In spite of great respect along with excitement, I am marking the end of the semester in my final year of a bachelor's degree by beginning my practical training at Jayamas Property Sdn. Bhd., a housing and property company that operates in the sale of properties like affordable homes, condominiums, and other types of products investments like hotels and serviced apartments. I was given a variety of duties and job scopes as a marketing trainee at Jayamas Property Sdn Bhd. In addition, I am being taught how to perform administrative duties that involve paperwork, and other marketing activities while receiving a lot of intrinsic and extrinsic benefits. My internship's purpose is to assess and conduct the company's strengths, weaknesses, opportunities and threats from terms of social, technological, and economic factors. The strength of Jayamas in terms of reputation and a strong and broad corporate portfolio has to be highlighted in this report. Of course, it is also possible to pinpoint the company's weaknesses such as its limited staff size and limited technology integration. There are some opportunities to seize, such as joint ventures and market expansion. Then, among the acknowledged threats are intense competition and reliance on market conditions. The company is recommended to sustain the company's success and strength by acting with integrity and exploring diversification. Next, to overcome internal weaknesses, the company should do training initiatives and utilize the internet of things (IoT). Do market analysis and attend events to take advantage of opportunities. Lastly, overcome the threats by concentrating on uniqueness and form partnerships.